O conceito de eu na filosofia crítica teórica de Kant - Kurle, Adriano Bueno (2012)
This paper deals with the concept of "self" in the "critical" period of Immanuel Kant's theoretical philosophy. The analysis focuses on the Critique of Pure Reason text. Drawing a distinction between empirical, rational and transcendental psychology (to which the paradigm of analysis of Kant belongs), it begins with an attempt to determine cognitive subject's place and character in the genesis of the transcendental epistemology. Pointing out the essentiality of the psychological aspects to a correct textual interpretation, even when they refer to transcendental psychology, it supports the idea that a purely semantic analysis of the Critique of Pure Reason text cannot lead to a legitimate interpretation. Subsequently, a description of the transcendental idealism doctrine is presented, in which the differences between the transcendental and realistic (or transcendent) perspectives are discussed, followed by the rise of two different ways to understand objects: as phenomenon and as noumenon. Following that, an analysis on the limits of knowledge is developed, also centering on ways of thinking the theory's subject itself in relation to those limits. Three distinct perspectives of the "self" approach arise: phenomenal self, transcendental self and noumenal self, each one's analysis being presented separately. Firstly, the phenomenal self and the relation between the intuition of space and time as an essential factor to think the unity of time in a continuous timeline, on which one can identify the chronological sequence of events and that allows us to reflect on the empirical permanency of the "self" in inner sense; secondly, the analysis of the transcendental self, which begins with a basic introduction to the faculty of understanding, its spontaneity and the synthesis ability and its importance to theme comprehension and finally brings up the concept of transcendental apperception and the distinction between conscience's unity and conscience's identity, from which our transcendental concept of "self" can be determined. The analysis also deals with four critics' (Strawson, Henrich, Pippin and Patricia Kitcher) view on transcendental apperception and conscience's identity; lastly, the noumenal self and the psychological understanding of "soul", according to its two kinds of use: constitutive and regulative.